A NARRATIVE ANALYSIS ON EXPERIENCES AS MIGRANT WORKERS IN SELANGOR, MALAYSIA - SITI SARRAH, ABDUL MOHSIN (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study aims to analyse construction of identity, the strategies employed in the process and common themes found in autobiographical narratives of migrant workers. The methodology used in this research includes semi-structured interviews, narrative analysis and thematic analysis. The interviews were carried out on 15 migrant workers from Indonesia, Bangladesh and Pakistan in order to obtain narrative data. Data were later analysed using Bamberg’s 3-Level of Positioning Theory (1997) for narrative analysis and Braun and Clarke’s Six-Phases of Thematic Analysis (2006) for thematic analysis. Findings from the study shows that participants employed discursive strategies such as direct positioning, involvement and collectivisation and linguistics devices such as constructed dialogue, pronoun and attributes during identity construction and management. Meanwhile, there are three overarching themes that were identified: motivation for migration, identity as a migrant worker and life as a migrant worker.